Optimization of Geothermal Binary Cycle Technology: an Review - Atifah Hirahmah; Putri Nabila; Serli Ahzari; Hamdi Hamdi (Journal of Renewable Energy, Electrical, and Computer Engineering, 2025)
Geothermal energy is mostly stored in the earth's interior, cost-effective and reliable compared to other sustainable energies, such as solar, wind and nuclear energy. Geothermal energy or geothermal energy is a competitive alternative energy because it is available in very large potential, can be used in the long term, and is environmentally friendly. This research uses descriptive quantitative methods with a data analysis and mapping process approach. The articles used in this research were articles published in the 2018-2023 range, totaling 50 articles. The articles are collected and then saved in *.ris format. Next, researchers used VOSviewer. Furthermore, this application suggests that the use of applications using Vosviewer is an application that is widely used to search for the latest research. Therefore, in this research the topic of optimization and zeotropic mixture